The Study of Electronic Properties of Perovskite with Methylammonium and Caesium Cation using Density Functional Theory Relativistic - agus rifani; Lana Ainunnisa (LPPM ITK, 2022)
Perovskite has developed as a photovoltaic material. Its power conversion energy has reached 22,1%. One of the perovskite materials was perovskite with methylammonium cation. But, the material has low thermal stabilization, so it needs to evolve by switching cations like cesium. Hence, further research is necessary to compare the electronic structure of both perovskite material to understand how efficiency increase by changing its cation using computational material methods. The computation was done using the ab-initio method with Density Functional Theory (DFT) formulation, Generalized-Gradient Approximation (GGA) as XC functional, and electron-ion core interaction modeled by pseudopotential (PP) relativistic data. The computational results show that MAPbI3 and CsPbI3 have direct band gaps of 1,64 eV and 1,46 eV. The cation switching from MA to Cs has decreased band gap value and generated electron-hole couples, represented by the curvature of the density of states (DOS).